2014
DOI: 10.3109/0284186x.2014.974826
|View full text |Cite
|
Sign up to set email alerts
|

Impact of changing rectal dose volume parameters over time on late rectal and urinary toxicity after high-dose intensity-modulated radiotherapy for prostate cancer: A 10-years single centre experience

Abstract: AbstrActbackground. External beam radiotherapy is an excellent treatment for patients with prostate cancer (PC). Assessing long-term radiotherapy-induced toxicity is important. We evaluated the impact of implementing different rectal dose volume constraints (DVC) on late rectal and urinary toxicity. Material and methods. Six hundred and thirty-seven PC patients were treated with high-dose intensity-modulated radiotherapy (IMRT) in the primary (median dose of 78 Gy to the prostate) or postoperative setting [med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
(2 reference statements)
3
7
0
Order By: Relevance
“…Incidence of late grade 3 GI toxicity was low, which is in agreement with similar IMRT studies ( Table 5 ). Fonteyne et al 26 reported a 1% late grade 3 GI toxicity with median of 5 years of follow-up for 232 patients who were treated with IMRT postoperatively, which is comparable with our finding of 2%. However, many IMRT series with lower patient numbers report 0% late grade 3 GI toxicity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Incidence of late grade 3 GI toxicity was low, which is in agreement with similar IMRT studies ( Table 5 ). Fonteyne et al 26 reported a 1% late grade 3 GI toxicity with median of 5 years of follow-up for 232 patients who were treated with IMRT postoperatively, which is comparable with our finding of 2%. However, many IMRT series with lower patient numbers report 0% late grade 3 GI toxicity.…”
Section: Discussionsupporting
confidence: 92%
“…2011 17 136 136 60 56% In-house toxicity score G2: 15% G3: 0% G2: 13% G3: < 1% G2: 28% G3: 3% G2: 31% G3: 3% Stricture: 6% G3: 1% Fonteyne et al. 2015 (combined 16 and 17) 26 232 232 60 NR In-house toxicity score NR G2: 11% G3: 1% NR G2: 26% G3: 6% G2: 2% Current Study 313 313 55 59% CTCAE v4.0 G2: 33% G3: < 1% G2: 16% G3: 2% G2: 25% G3: 0% G2: 37% G3: 10% G3: 5% bPFS, biochemical progression-free survival; CTCAE, Common Terminology Criteria for Adverse Events; FU, follow up; G, grade; GI, gastrointestinal; GU, genitourinary; IMRT, intensity modulated radiation therapy; NR, not reported; RTOG, Radiation Technology Oncology Group. a Rates include both patients were treated with IMRT and those who were not.…”
Section: Discussionmentioning
confidence: 99%
“…The development of ever more elaborate normal-tissue complication probability (NTCP) models is driven by the concern that a poor characterization of the dose-response relationship may unnecessarily limit the effectiveness of the treatment; a simplistic NTCP model could imply conservative dose-volume constraints to the organs-at-risk (OAR), or cause avoidable suffering through a suboptimal distribution of the dose to OAR for a given tumor dose (e.g., Ref. [18]). Reliable NTCP models can also be used to optimize the treatment strategy [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology behind such RT-induced injuries is, however, not extensively understood [14]. Typically, the risk of RT-induced GI morbidity is described by dose/volume parameters of the rectum [7,1517]. Novel but less recognized approaches involve for example addressing dose surface/wall distributions of the rectum [1820], and studying pathophysiological properties.…”
Section: Introductionmentioning
confidence: 99%